Palsy a lithalsy, proč ano, proč ne v minulosti v Krkonoších - Kociánová, M.; Jankovská, V. (Vlasta); Štursová, H. (2010)
This article discuss the question of possible existence of palsas, lithalsas and the other cryogenic forms in the Giant Mts. during the Pleistocene/Holocene. There were used own experiences gained during field – works in areas where recent palsas exist [there are territories of discontinuous permafrost Polar Ural Mts, Kola and Yamal Peninsula, northwest Siberia, central Norway, northern Sweden and Finland]. Part of field – works consisted of digging a palsas and lithalsas profiles, measuring the active layer depth, taking samples for palynological and granulometric analyses, description of vegetation cover etc. The conclusion is: in the Giant Mts on Pančava mire, Upske mire and Stribrna bystrina mire some relief forms resemble palsas, however only by shape – not by origin. In conditions of seasonaly freezing mires their origin is other than predominantly cryogenic. Terms „palsa“ or „palsa-like“ can not be used here in any case.